IMPLEMENTASI PERATURAN WALIKOTA PEKANBARU NOMOR 30 TAHUN 2016 DALAM MEWUJUDKAN PASAR INDUK DI KOTA PEKANBARU 2016-2021 - Robisendriadi "; Isril " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
Regional development planning is not always successful in fulfilling regional desires. The reality is that the development carried out by each region takes a long time, and of course, in this long process, there are many obstacles, barriers, challenges, and obstacles in its implementation. The purpose of this research is to describe the implementation of Pekanbaru Mayor Regulation Number 30 of 2016, which has not been realized, the causes of development failures, and the government's actions in overcoming them. This study uses a qualitative approach and in-depth analysis techniques. The data collection techniques used in this study were interviews and documentation. The data obtained from this study came from two sources, namely primary and secondary. The results of this study show that in the implementation process, there are several obstacles to development, including communication errors, inadequate resources from the Pekanbaru City Government, the disposition or attitude of workers or builders on the part of the developer, which interferes with the work process, and the bureaucratic structure of the consultant supervisor. To address this, the government has issued an addendum allowing for additional processing time until 2019, issued warnings, and mediated with the surrounding community. So, according to the findings of this study, the implementation of Pekanbaru Mayor Regulation Number 30 of 2016 in realizing a main market in Pekanbaru City from 2016 to 2021 still faces significant challenges, and the Pekanbaru city government must be responsive in responding to this. Keywords: Implementation, Central Market, Mayor Regulation